Synthesis, Biological Evaluation, Molecular Dynamics, and QM-MM Calculation of Spiro-Acridine Derivatives Against Leishmaniasis - Sonaly Albino; Michelangela Nobre; Jamire da Silva; Malu dos Reis; Maria Nascimento; Mayara de Oliveira; Tatiana Borges; Lucas Albuquerque; Selma Kuckelhaus; Luis Alves; Fábio dos Santos; Maria de Lima; et al. (Microorganisms)
Leishmaniasis is a neglected tropical disease caused by Leishmania sp. The therapeutic arsenal is reduced and limited. In this context, acridine derivatives present themselves as promising leishmanicidal compounds. This paper involved synthesizing and evaluating the antileishmanial and immunomodulatory potential of spiro-acridine derivatives. Six spiro-acridine derivatives were obtained through nucleophilic substitution reactions between the acetohydrazide/acetamide intermediates and 9-carbaldehydeacridine, followed by spontaneous cyclization. IR, NMR, and HRMS confirmed the structures. These were analyzed in vitro against L. infantum and L. amazonensis to determine anti-promastigote, anti-amastigote, and cytotoxicity effects. Immunomodulatory activity was evaluated using CBA, DCF-DA, and DAF-FM diacetate. In silico evaluation included molecular docking and dynamics. The spiro-acridines showed a wide range of anti-promastigote activities (IC50 = 0.73–234.95 µM) and non-toxicity to red blood cells. AMTAC-02 and ACMD-03 demonstrated satisfactory anti-amastigote effect (IC50 = 10.47–13.50 µM), low toxicity to macrophages (CC50 = 27.22–569.50 µM), and cytokine and reactive species modulation. Molecular docking proposed cysteine protease B of L. amazonensis as a target, and molecular dynamics analysis highlighted the complex’s stability using RMSD, Rg, SASA, DCCM, PCA, and MM-PBSA (ΔG = −65.225 kJ/mol). Furthermore, QM-MM calculation provided the best energy for ACMD-03 (−199.30 au). Hence, AMTAC-02 and ACMD-03 demonstrated antileishmanial potential, making them promising entities for the development of leishmanicidal drug candidates.